2011
DOI: 10.1007/s12975-010-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment with Candesartan Reduces Early Injury After Permanent Middle Cerebral Artery Occlusion

Abstract: We have shown that reduction of blood pressure (BP) immediately after the onset of reperfusion reduced neurovascular damage and improved functional outcome after experimental cerebral ischemia and candesartan is particularly effective in improving long-term functional outcome. In this study, we sought to determine if early BP lowering with candesartan, in the presence of an occluded cerebral artery, will reduce injury and improve outcome after experimental stroke. Male Wistar rats underwent 24 h or 7 days of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…Inhibition of metalloproteinase (MMP)-2 and MMP-9 reduces neuronal and glial apoptosis [59]. Furthermore, Guan et al reported that MMP-2, MMP-9, and vascular endothelial growth factor (VEGF) are significantly increased by MCAO, but candesartan fails to reduce MMP-2, MMP-9, and VEGF in the rat MCAO model [60]. These findings show that telmisartan, irbesartan, and candesartan reduce infarct size and improve neurological outcome in ischemic stroke model rats.…”
Section: Experimental Studies Of Arbsmentioning
confidence: 99%
“…Inhibition of metalloproteinase (MMP)-2 and MMP-9 reduces neuronal and glial apoptosis [59]. Furthermore, Guan et al reported that MMP-2, MMP-9, and vascular endothelial growth factor (VEGF) are significantly increased by MCAO, but candesartan fails to reduce MMP-2, MMP-9, and VEGF in the rat MCAO model [60]. These findings show that telmisartan, irbesartan, and candesartan reduce infarct size and improve neurological outcome in ischemic stroke model rats.…”
Section: Experimental Studies Of Arbsmentioning
confidence: 99%
“…The difference in the efficacy of 1 mg/kg/day between our data and that of Timaru-Kast et al (2012) may be explained by different mechanisms of administration. There is a significant drop in blood pressure following TBI that could be detrimental (Guan et al, 2011;Sookplung et al, 2011). Thus, medication that lowers blood pressure further may be problematic in treating TBI.…”
Section: Neuroprotection By Candesartan After Tbimentioning
confidence: 99%
“…We hypothesized that treatment with candesartan may improve the behavioral and neurological outcome after TBI, in a manner similar to that observed in rodent models and in humans affected by stroke (Awad, 2011;Guan et al, 2011;Ito et al, 2001;Liu et al, 2008;Stenman and Edvinsson, 2004). We therefore investigated the effect of administering candesartan to mice just before they received a controlled cortical impact (CCI) injury to determine whether short-or long-term inhibition of central AT 1 Rs would reduce the cortical and hippocampal damage and hence protect against cognitive impairment.…”
Section: Introductionmentioning
confidence: 96%
“…Scanning laser Doppler (Pim-3, Perimed, ST) was used to confirm a similar degree of drop in CBF among groups. The percent drop in CBF after stroke was determined by comparing to baseline [24]. To monitor the ability of tPA to resolve the blood clots and restore blood flow, CBF was measured 30, 60 and 120 minutes after tPA administration in animals subjected to thromboembolic occlusion.…”
Section: Methodsmentioning
confidence: 99%